Computed tomography and other imaging modalities in pediatric congenital heart disease - Hongying, Chen; Bahari, Norafida; Mohamad Saini, Suraini; Mohd Noor, Noramaliza (UPM Press, 2022)
Congenital heart defects (CHD) are the most common congenital disabilities. Early and accurate diagnosis of coronary heart disease is very important for patients to get timely and effective treatment. In recent years, the accuracy of coronary heart disease diagnosis has been greatly improved with the development of medical imaging equipment and technology. At present, the clinical application of echocardiogram (echo), cardiovascular magnetic resonance (CMR) and computed tomography angiography (CTA) in coronary heart disease anatomy and function has increased significantly, which plays an important role in preoperative diagnosis, intraoperative monitoring, and postoperative recovery evaluation. However, each imaging technique has its indications. Providing the best examination plan for patients requires clinicians and radiologists’ close cooperation. Therefore, this study reviewed the imaging techniques for diagnosing coronary heart disease.